Proposição de elementos estruturantes para contratos administrativos entre o poder público e empreendimentos de catadores de resíduos recicláveis no Brasil - Domingues Junior, José Olimpio (Universidade Federal de São Carlos, 2022)
The evolution of the urbanization process and the disorderly growth of cities resulted in numerous environmental problems worldwide, among which stands out the significant increase in waste production, as well as its inadequate disposal. With the enactment of the National Solid Waste Policy (PNRS) in 2010, there was the regulation of services for the management and treatment of urban solid waste, which aims to mitigate the Brazilian environmental problems related to the inadequate disposal of urban waste, having as one of the principles to the social inclusion and economic emancipation of collectors of reusable and recyclable materials. This legislation advocates direct contracting between city halls and waste picker enterprises to carry out selective collection. Within the scope of the solid waste chain, there is fundamentally the articulation between solidary undertakings, public authorities and private entities that work in the process of collecting, sorting and processing solid waste in the municipality. The collectors play an important role in this stage. This thesis aimed to propose structuring elements in administrative contracts between the public authorities and recyclable waste pickers in Brazil. The research methodology corresponded to the descriptive approach, through the following methods: consultations with publications (articles, theses, dissertations, websites of city halls and cooperatives); survey of empirical variables organized into variables related to contracts (RC) and the list of contracted agents (CA); definition of variables and subvariables; quantitative data analysis techniques - Cohort and information value. The results showed that the contractual instruments are not in accordance with the devices and aspects recommended by the PNRS, due to the lack of social, economic and environmental inclusion of the collectors, recognition of the work of these professionals, integration into the municipal system in the management of solid waste. It was concluded that the number of contracts entered into between city halls and waste pickers should advance, since they are at odds with what the PNRS recommends, in which it establishes and encourages this contract to assist in the management of urban solid waste. In addition, there must be an instrument that enables and promotes the re-signification of waste pickers' undertakings. For that purpose, seven devices with structuring elements were proposed with the intention of being a reference and contributing to the public administration and waste pickers' enterprises, by helping such agents in the formulation and development of the draft of the contractual instruments. The main contribution of this study is to highlight the possibilities of advances, both in the quantitative and qualitative aspects of contracting between public authorities and waste picker enterprises by pointing out structural elements that allow the protection of such entities and, especially, the pickers, by allowing improvements in conditions of life and work, in addition to promoting quality in the provision of services in the area of urban solid waste.
Proposal of structuring elements for administrative contracts between the government and enterprises of recyclable waste collectors in Brazil
Keywords: Collectors' cooperatives; Contracts with cooperatives; Selective collect; Recyclable waste.; ENGENHARIAS::ENGENHARIA CIVIL; ENGENHARIAS